PENERAPAN METODE BERNYANYI UNTUK MENINGKATKAN FOKUS ANAK DALAM BELAJAR DI PENDIDIKAN ANAK USIA DINI KASIH IBU DESA RAMBUTAN MASAM KECAMATAN MUARA TEMBESI KABUPATEN BATANGHARI - Dina Aprilioni; Mahluddin; Husin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Early childhood is a period of very rapid development, therefore requiring appropriate learning stimulation. One important aspect of the early childhood learning process is learning focus, as children’s focus during learning activities is a crucial factor influencing learning success. However, based on observations conducted at PAUD Kasih Ibu, Rambutan Masam Village, Muara Tembesi District, Batang Hari Regency, it was found that some children showed a lack of focus during learning activities, such as being easily distracted, paying less attention to the teacher’s explanations, and showing low active participation in learning. This study aimed to determine the extent to which the singing method can improve focus in early childhood. The subjects of this study were 11 children from Group A. This research employed Classroom Action Research (CAR), which was conducted in two cycles, with each cycle consisting of two meetings. Data collection techniques included observation, interviews, and documentation. The data were analyzed using descriptive qualitative analysis and simple quantitative analysis. The results showed a significant improvement in children’s learning focus. In the pre-cycle stage, the average level of children’s developmental achievement was 27%, which increased to 64% in Cycle I. Furthermore, in Cycle II, the achievement increased to 82%. These improvements indicate that the singing method can be used as an effective alternative learning strategy to enhance children’s focus in the teaching and learning process.